1999
DOI: 10.1080/02839319950162679
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nutritional Status and Physical Activity, Ulcer History and Ulcer-related Problems in Patients with Leg and Foot Ulcers

Abstract: The nutritional status in patients with leg and foot ulcers is assessed in relation to sociodemographic data, mobility, physical activity, ulcer history, and ulcer-related problems from the patients' point of view. The patients (20 men and 50 women, mean age 79 years) were living in their own homes and treatment was given in primary health care. The Mini Nutritional Assessment (MNA) was used to assess nutritional status. Interviews were conducted to collect data on patients' mobility, physical activity, ulcer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
1
15
0
2
Order By: Relevance
“…The MNA has been found to predict length of hospital stay, costs (Pertoldi et al, 1996), and mortality (Beck et al, 1999;Comban et al, 1999). The tool has been used in elderly Swedish people receiving primary health care (Wissing & Unosson, 1999) and those in home nursing care (Saletti et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The MNA has been found to predict length of hospital stay, costs (Pertoldi et al, 1996), and mortality (Beck et al, 1999;Comban et al, 1999). The tool has been used in elderly Swedish people receiving primary health care (Wissing & Unosson, 1999) and those in home nursing care (Saletti et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This is probably so because orange juice for breakfast and vegetables and fruit within evening meals are not very common among the elderly. It has been shown that potatoes form the major source of vitamin C, with very little being obtained from fruit or fruit juices in elderly patients with venous leg ulcers ( Lewis et al ., 1993 ). Low levels of vitamin C in leucocytes ( Lewis et al ., 1993 ) and a serious deficiency of the vitamin have been seen in patients with leg ulcers ( Balaji & Mosley, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…If an individual is unable to get or to eat the nutrients required, malnutrition will occur sooner or later. Various studies indicate that patients with chronic leg ulcers are at risk of malnutrition ( Lewis et al ., 1993 ; Balaji & Mosley, 1995; Wissing & Unosson, 1999). Diseases and restrictions in mobility may decrease the leg ulcer patient’s ability to purchase and prepare their own food.…”
Section: Introductionmentioning
confidence: 99%
“…One concerned not acutely ill elderly visiting their general practitioner (Beck et al, 2001), and the other reported elderly with foot ulcers contacted for research purposes (Wissing & Unosson, 1999). The prevalence of undernutrition was 0 and 3%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The inter-reviewer kappa was 0.68 (95% confidence interval (CI): 0.54-0.83). From the references of the initially included articles, we included one additional study (Wissing & Unosson, 1999). Articles were excluded because they did not describe prevalence studies (eg narrative reviews) or did not concern a general practice population (eg community dwelling).…”
Section: Methodsmentioning
confidence: 99%